Trends in utilization of benzodiazepine and Z‐drugs in Israel. Issue 12 (13th October 2017) - Berman, Erez; Eyal, Sara; Marom, Eli
Abstract: Background: Studies on benzodiazepine (BZDs) as well as Zopiclone and Zolpidem (Z‐drugs) utilization are important for estimating the prevalence of medical conditions, providing the basis for pharmacovigilance, and identifying temporal trends of consumption. Such studies that involve the Israeli population have not been conducted yet. Purpose: Identify trends over time in utilization of BZDs and Z‐drugs in a nationwide population in Israel. Methods: Data on BZD and Z‐drugs utilization (for all indications) for the period 2005 to 2013 were obtained from pharmaceutical companies that distribute BZDs in Israel. Prevalence of BZD utilization was reported as defined daily doses (DDD)/1000 inhabitants/day. Results: The utilization of BZDs and Z‐drugs aimed to treat sleeping disorders increased over the period of the study from 10.22 to 22.49 DDD/1000 inhabitants/day. The greatest increases in utilization of drugs established in Israel were observed for brotizolam (83%), zopiclone (59%), and zolpidem (94%). Decreases in use were recorded for lorazepam (14%), diazepam (16%), and oxazepam (27%). Use of hypnotic BZDs appeared to be relatively high, compared with the use of non‐BZD hypnotics ("Z‐drugs") such as zolpidem or zopiclone. Nationwide stressful conditions did not appear to be reflected in the annual BZD sales. Conclusions: Conventional BZDs and Z‐drugs remained the treatment of choice for sleeping disorders in Israel during the study period. These results are, in certain cases, in contrast to current practice recommendations and guidelines and point at a need in better dissemination of these guidelines among prescribers in Israel.